Employee’s Perceptions on Occupational Safety and Health Management System (OSHMS) in A Wood Based Product Manufacturing Company - ADENAN, NUR SYAHIRAH; RAHIM BIN JAMIAN; MOHD HAFIZUDDIN BIN WAHAB (Progress in Engineering Application and Technology, 2023)
Occupational accidents are among the most crucial employment issues in most workplaces of manufacturing companies. One of the factors encountered to influence safety compliance is employee perception on workplace safety. Previous studies reveal that employee perceptions of safety and health at work are important because they have been associated with better adherence to safe work behaviors and a few accident related injuries and illnesses. This study seeks to provide an empirical evidence on the perceived employee safety awareness and satisfaction towards occupational safety and health management system (OSHMS) in a selected chipboards manufacturing company. This study employs quantitative research method, specifically survey questionnaires. The overall results of the study revealed that most employees showed positive perceptions towards OSHMS in the company. By examining how employees perceive OSHMS, the findings contributed to significant practical implications for manufacturing companies looking to improve every aspect of OSHMS implementation.